PENGARUH KOMPOS ECENG GONDOK DAN PUPUK FOSFOR TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Vignaradiata L.) - Monanda, Ade Ressi; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to know the interaction and get the best dose of water hyacinth compost andphosphorus fertilizer to the growth and yieldof mung bean. This research conducted in UPT area of research farm in faculty of agriculture, Riau Universityfrom March 2015 until June 2015.This research used a randomized block design with 2 factors and three replications. The first factor is the dose of water hyacinth compostconsist of 4 levels (K0= 0 ton/ha, K1= 5 ton/ha, K3= 10 ton/ha, K4=15 ton/ha). The second factor is the dose of phosphorus fertilizer that consist of 5 level: (P0= 0 kg TSP/ha, P1= 25 kg TSP/ha, P2= 50 kg TSP/ha. P3= 75 kg TSP/ha, P4= 100 kg TSP/ha).Parameters measured were plant height, number of branch, flowering time, pods number per plot, the percentage of pithy pods, weight of 100 seeds and production per plot. Data were analyzed statistically using ANOVA and followed with DNMRT at level of 5%. The result showed the interaction between giving water hyacinth compost and the phosphorus fertilizer increasedpods number per plot, weight of 100 seeds and production per plot. Water hyacinth compost dose 15 ton/ha and phosphorus fertilizer dose 75 and 100 kg TSP/ha showed the best result inrate ofplant height, number of branch, pods number per plot, weight of 100 seeds and production per plot (1,5 m2) which is the best production per plot is 469,73 g/plot (3,1 ton/ha).   Keywords : Mungbean, water hyacinth compost, phosphorus fertilizer, growth and yield.